EFEKTIVITAS PEMBERIAN JAHE HANGAT TERHADAP FREKUENSI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I TAHUN 2024 - Muliani, Rima; Paridah, Siti (Journal of Midwifery Tiara Bunda, 2025)
Background: Emesis gravidarum is said to be normal, but if it cannot be properly monitored and treated, it can lead to a more serious condition, namely hyperemesis gravidarum which can affect fetal development. Symptoms of emesis gravidarum can be treated with both conventional and non-conventional treatments such as giving warm ginger drinks.. Research Objective: To determine the effectiveness of giving warm ginger on the frequency of emesis gravidarum in warm pregnant women at the Cipari Health Center, Sukabumi Regency in 2024. Research Method: This research uses a Quasi Experimental type with a One Group Pre Test and Post Test design. The sample in this study was 30 pregnant women in the first trimester who experienced emesis gravidarum at the Cipari Health Center, Sukabumi Regency and the sampling technique used purposive sampling. Results: The results of the study show that the frequency of emesis gravidarum in pregnant women in the first trimester before giving warm ginger I at the Cipari Community Health Center, Sukabmi Regency in 2024, on average, experienced moderate emesis gravidarum after giving warm ginger, on average they experienced mild emesis. The Wilcoxon test results have a P-Value of 0.000. Conclusion: There are differences in the frequency of emesis gravidarum among pregnant women in the first trimester at the Cipari Health Center, Sukabmi Regency in 2024